Krisztina Egerszegi's Full Stroke at 120 m of Her 200 m Backstroke Gold Medal Swim at the Barcelona Olympic Games 1992 - Rushall, B. S. (1999)
Video pictures (14 frames) and the appropriate technical/ biomechanical explanations for Krisztina Egerszegi's Full Stroke at 120 m of Her 200 m Backstroke Gold Medal Swim at the Barcelona Olympic Games 1992. The characteristics of the other sequences of Krisztina Egerszegi's swimming are evidenced here. The different movement patterns of each arm, the role of the kick to produce hip and shoulder rotation and to offset lateral and vertical force components created by the arm movement can be seen. Her head is deeper and flatter in the left arm stroke than during the right arm stroke. Krisztina Egerszegi's stroking pattern is consistent between her 100 m and 200 m swimming performances.